2019
DOI: 10.1097/njh.0000000000000482
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validity of the Nursing Care Scale and Nurse’s Difficulty Scale in Caring for Dying Patients With Cancer and Their Families in General Hospitals in Japan

Abstract: This study develops and examines the validity and reliability of 2 scales, respectively, for evaluating nursing care and the experience of difficulties providing nursing care for dying patients with cancer and their families. A cross-sectional anonymous questionnaire was administered to nursing staff caring for dying patients with cancer and their families in 4 general hospitals and a university hospital in Japan. The instruments assessed were the Nursing Care Scale for Dying Patients and Their Families (NCD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
(36 reference statements)
0
2
0
2
Order By: Relevance
“… 20 Our results were consistent with that of the original PCDS, showing fairly good validity when compared with similar tools. 12 , 27 …”
Section: Discussionmentioning
confidence: 99%
“… 20 Our results were consistent with that of the original PCDS, showing fairly good validity when compared with similar tools. 12 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…This subscale represents a skill used to convey the meaning and content of a conversation to end-stage patients and their families, to promote dialogue and to build a relationship with the patients. Kanno et al 26 identified “explanation to the family” as a component of difficulty scale in end-of-life care, experienced by general ward nurses. The present study demonstrated that “verbal communication skills for good communication” are a valid factor in addressing difficulties and promoting support for the transition to homecare settings.…”
Section: Discussionmentioning
confidence: 99%
“…Esta prueba indica la consistencia interna, muestra si los elementos miden la misma calidad y si los elementos están relacionados con el sujeto a medir. Para que se considere suficiente en una medición, el coeficiente de fiabilidad debe ser lo más cercano posible a 1 (23). Para la validación del test PCDS, se aplicó un análisis factorial exploratorio (EFA) con la prueba de Kaiser-Meyer-Olkin (KMO) la cual se encarga de comparar el valor de los coeficientes de correlación con la magnitud de los coeficientes de correlación parcial (24).…”
Section: Métodosunclassified